2019
DOI: 10.1002/jcp.29133
|View full text |Cite
|
Sign up to set email alerts
|

CLDN1 induces autophagy to promote proliferation and metastasis of esophageal squamous carcinoma through AMPK/STAT1/ULK1 signaling

Abstract: Tight junction is a structural constitution in cell-cell adhesion and play an important role in the maintenance of permeability and integrity of normal epithelial cell barrier.The protein encoded by Claudin 1 (CLDN1), a member of the claudin family, is an integral membrane protein and a component of tight junction strands. CLDN1 has been proved to regulate the proliferation and metastasis of multiple tumors, but little is known about its role in esophageal squamous cell carcinoma (ESCC). Here, we found that CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…In addition, other studies have suggested that STAT1 promotes tumor growth by inhibiting tumor immune surveillance and by promoting tumor resistance against chemotherapy and irradiation. For example, activation of STAT1 by the cancer-up-regulated gene 2 enhances metastasis and drug resistance in colon cancer cells (42)(43)(44). Taken together, these data suggest that JAK-STAT activity is likely cancer type-dependent, especially in CRC.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, other studies have suggested that STAT1 promotes tumor growth by inhibiting tumor immune surveillance and by promoting tumor resistance against chemotherapy and irradiation. For example, activation of STAT1 by the cancer-up-regulated gene 2 enhances metastasis and drug resistance in colon cancer cells (42)(43)(44). Taken together, these data suggest that JAK-STAT activity is likely cancer type-dependent, especially in CRC.…”
Section: Discussionmentioning
confidence: 83%
“…[1,21] In addition, a previous study revealed that aberrant expression of CLDN1 regulated AMPK/STAT1/ULK1 signaling pathway, lead to the promotion of proliferation and metastasis in esophageal squamous cancer. [29] Moreover, CLDN1 was experimentally demonstrated remarkably upregulated in CRC patients and could be considered as methylated diagnostic biomarker in CRC and normal control groups. [17] 2) EPHX4 (Epoxide Hydrolase 4) is a protein coding gene, which was signi cantly upregulated in rectal cancer con rmed by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased or decreased expression levels of CLDN1 have been found to be associated with several types of tumor; for example, overexpression of CLDN1 has been observed in nasopharyngeal, ovarian and oral squamous cell cancer (29). A number of studies have revealed that CLDN1 upregulation may contribute to tumor progression in esophageal squamous cell carcinoma, colon cancer and gastric carcinoma (30)(31)(32), while in other types of cancer, such as lung adenocarcinoma, CLDN1 acts as a tumor suppressor by activating the expression of matrix metallopeptidase-2 and high CLDN1 expression is associated with an improved prognosis (33). In prostate adenocarcinoma, Sheehan et al (34) demonstrated that patients with loss of CLDN1 protein expression had a higher rate of disease recurrence.…”
Section: Effect Of Claudin 1 On Cell Proliferation Migration and Apomentioning
confidence: 99%